Enrichment of adenosine using thermally responsive chromatographic materials under friendly pH conditions. Issue 23 (17th November 2015) - Liang, Yanli; Geng, Fangfang; Dai, Rongji; Deng, Yulin
Abstract : A thermally responsive boronate affinity chromatographic material, which showed thermal sensitivity, had been successfully applied for the enrichment and separation of cis‐ diol‐containing compounds, and the capture and release process could be facilitated by adjusting the temperature. However, in this system, the pH of the mobile phase must be higher than 9.8, and alkaline media can lead to the degradation of labile compounds; the use of silica beads also limits its use. In this study, thermally responsive boronate affinity chromatographic material, namely poly( N‐ isopropylacrylamide‐co‐ N ‐acryloyl‐3‐aminophenylboronic acid) grafted silica, was successfully prepared by atom transfer radical polymerization. Its structure was confirmed by IR spectroscopy and the graft ratio was 20.8%, determined by thermogravimetric analysis. Furthermore, the capture/release of adenosine, a cis ‐diol, was performed from pH 5.0–9.0 and 10–50°C. The elution of adenosine was remarkably retarded at decreased temperatures and adenosine could be captured completely at 10°C at pH values of 5.0–9.0. The enrichment of adenosine could be achieved by simply changing the temperature from 10 to 50°C. Therefore, this material not only improved the stability of the silica, but was also suitable for the capture of oxidation‐sensitive biological analytes. Moreover, it could be used for the enrichment of cis ‐diol‐containing compounds in LC with MS.